Life-threatening immune checkpoint inhibitor-induced myocarditis and myasthenia gravis overlap syndrome treated with abatacept: a case report. Issue 11 (2nd November 2021) - Wakefield, Chelby; Shultz, Carl; Patel, Brijesh; Malla, Midhun
Abstract : We present here the second documented case of severe immune checkpoint inhibitor-induced myocarditis successfully treated with abatacept. The patient was started on pembrolizumab for stage IIIA malignant melanoma, and after the first dose was admitted for worsening shortness of breath and weakness. Her symptoms were refractory to high-dose steroids and she decompensated rapidly necessitating cardiopulmonary resuscitation and subsequent intubation and mechanical ventilation. Intravenous immunoglobulin and plasmapheresis did not invoke significant improvement, so abatacept was then initiated. She began to show improvement and was eventually discharged to a skilled nursing facility. This case highlights a severe adverse reaction to an immunomodulator class steadily growing in its application. Providers of all specialties should be aware of the side effects and treatment options. Our case demonstrates that continued investigation into the utilisation of CTLA-4 agonists in the treatment of severe adverse reactions like myocarditis caused by pembrolizumab is required.